Model Matematik Aliran Air Bawah Bendung - Pramudiyanto, Didik Purwantoro (Universitas Negeri Yogyakarta, 2007)
Dam is a structure which is the main function is to dammed up theflow ofthe river so that it gets the sum ofa specific volume ofthe water. The dam can be builtfrom concrete, stone, sand,. clay or combinations between them. As it function to resist the water flow ofthe river, the dam must be controlledfrom its displacement or turning over came fromthe water pressure. On the clay-typed dam, the safety value is also determinedfrom the water